MANAGEMENT FOR THE IMPLEMENTATION OF DEVELOPMENT PLANNING MEETINGS IN PETASIA DISTRICT, DISTRICT NORTH MOROWALI - Lapasila, Isna; Mangngasing, Nasir; Nuraisyah, Nuraisyah; Haryono, Dandan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
The objective of this research is to analyze the process and management involved in the implementation of Development Planning Deliberations in Petasia Sub-District. The research methodology used is a qualitative approach employing participatory observation techniques and in-depth interviews with selected informants directly involved in the Development Planning Deliberations in the area. Key informants include community leaders, local government representatives, community members, and other stakeholders involved in the deliberation process. The collected data will be analyzed using qualitative analysis techniques, including content analysis and data triangulation, to obtain a comprehensive understanding of the process and management of Development Planning Deliberations in Petasia Sub-District. The expected outcomes of the research aim to depict the dynamics, challenges, and decision-making processes within the Development Planning Deliberations. The conclusion of this study will outline key aspects influencing the effectiveness of deliberation implementation, along with recommendations for improving management and the development planning process in the future. The conclusion emphasizes the importance of efficiency, transparency, and active participation in Development Planning Deliberations in Petasia Sub-District, North Morowali Regency. Recommendations are provided to enhance management and the planning process for a more positive impact on the local community.